SENGKETA YERUSALEM ANTARA PALESTINA DAN ISRAEL (Faculty of Law, University of Dr. Soetomo, 2018)
US Presidential Decree Donald Trump announces the recognition of Jerusalem as the capital of Israel has sparked curses, criticism and opposition from various parties. The question arises as to what constitutes Trump's decision and what its impact on the world. What is the history behind the Jerusalem City dispute between Palestine and Israel. The question continues to emerge from various circles of people in the world. Why not? Donald Trump's statement unilaterally stated that Jerusalem became the capital of Israel, reaping many reactions. The final status of Jerusalem has always been one of the most difficult and instilling sensitive questions in the Israeli and Palestinian conflict. If the US declares Jerusalem as the capital of Israel, it seems to answer the question unilaterally. In fact, the issue will clash with the international consensus on the holy city. Recognizing Jerusalem as the capital of Israel is also one step ahead to move the US Embassy from Tel Aviv to Jerusalem which further strengthens Israel's sovereignty over the city. The transfer of US Embassy to Jerusalem could have been easy because the US also placed its consulate in Jerusalem, while the embassy building was in Tel Aviv. However, it is not as easy as turning the palm of the hand. Keyword : Israel, Palestina, Sengketa